2011
DOI: 10.1016/j.biortech.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Rapid start-up of thermophilic anaerobic digestion with the turf fraction of MSW as inoculum

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Stirring of the culture was not conducive for succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…1). The spontaneous methane production at 1.8 g Na + /L confirms the previously published observations that sufficient thermophilic acetate degrading methanogenic consortia are present in turf grass soil to enable a swift start-up of thermophilic anaerobic digestion (Suwannoppadol et al 2011). Methane production and acetate degradation was completely inhibited in the presence of 330 mM (7.8 g Na + /L).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…1). The spontaneous methane production at 1.8 g Na + /L confirms the previously published observations that sufficient thermophilic acetate degrading methanogenic consortia are present in turf grass soil to enable a swift start-up of thermophilic anaerobic digestion (Suwannoppadol et al 2011). Methane production and acetate degradation was completely inhibited in the presence of 330 mM (7.8 g Na + /L).…”
Section: Discussionsupporting
confidence: 88%
“…This study originated from observations that thermophilic anaerobic digestion can be started up successfully in the presence of high sodium bicarbonate concentrations (330 mM) added to avoid early build-up of volatile fatty acids (Suwannoppadol et al, 2011). It therefore appears that factors present in this type of digestions mitigate the usually observed inhibition by salt.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study (Suwannoppadol et al, 2011) found that thermophilic anaerobic incubation of turf grass, which consisted of a mixture turf grass species, exhibited a significant methanogenic activity within a few days of incubation. On the other hand, there was no methanogenic activity in samples seeded with mixed tree bark, tree leaves, or soil (away from grass lawn).…”
Section: The Presence Of Thermophilic Methanogens In Various Species mentioning
confidence: 94%
“…Freshly sampled mesophilic anaerobic sludge is a well-known inoculum used for starting thermophilic anaerobic digestion (Bolzonella et According to our previous study (Suwannoppadol et al, 2011), the Organic Fraction of Municipal Solid Waste (OFMSW) contains a suitable inoculum for start-up of thermophilic anaerobic digestion. The source of active thermophilic methanogens was narrowed to down to be part of grass clippings (grass turf) contained in the waste.…”
Section: Introductionmentioning
confidence: 99%
“…source of thermophilic inoculum, the start-up period of thermophilic anaerobic digestion 22 can be prolonged, with Ahring (1994) reporting up to one year for a reactor to reach 23 steady state. Suwannoppadol et al, (2011) found that, for thermophilic anaerobicwithin 3 days, and the system required approximately 5 days for acetate consumption to 1 exceed production. In the current study, CH 4 was produced (0.1L/L/d) within 24 h with 2 significant acetate consumption (> production) occurring within 3 days of the 3 commencement of digestion (Fig.…”
Section: Comparison Of Solid Degradation In Laboratory and Full-scalementioning
confidence: 99%